Fishery Ecolexicon in Kambera - Raynesta Mikaela Indri Malo (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
This research is a qualitative descriptive study that aims to study and describe the ecolexicon that represents the fisheries sector in Waingapu using ecolinguistics theory. This theory emphasizes the reciprocal relationship between language and the environment. The data collection methods used are in-depth interviews and observation. Data are analyzed using the padan method, specifically teknik pilah unsur penentu (the determinant element sorting technique). Informants are people who live and work in the fisheries sector, such as fishermen, fishmongers, and fishery practitioners. Data analysis shows that there are lexicons in Kambera related to the fishery sector which consists of nouns and verbs from the point of view of lexical categories. Nouns dominate the list and contain most of the names of fishery products such as fishes, crabs, clams, and others. Besides, it also consists of terms of fishing equipment. For verbs, they are related to fishing activities.